Thiosemicarbazone of lapachol acts on cell membrane in Paracoccidioides brasiliensis. (26th June 2018) - de Sá, Nívea Pereira; Cisalpino, Patrícia Silva; Bertollo, Caryne Margotto; Santos, Patrícia Campi; Rosa, Carlos Augusto; de Souza, Daniele da Glória; Barbeira, Paulo Jorge Sanches; Alves, Tânia Maria de Almeida; Zani, Carlos Leomar; Johann, Susana
Abstract: Paracoccidioidomycosis (PCM) is the most prevalent systemic mycosis in Latin American countries. Amphotericin B, sulfonamides, and azoles may be used in the treatment of PCM. However, the high toxicity, prolonged course of treatment, and significant frequency of disease relapse compromise their use. Therefore, there is a need to seek new therapeutic options. We conducted tests with thiosemicarbazone of lapachol (TSC-lap) to determine the antifungal activity and phenotypic effects against several isolates of Paracoccidioides spp. In addition, we evaluated the toxicity against murine macrophages and the ability to enhance phagocytosis. Further, we verified that TSC-lap was active against yeasts but did not show any interaction with the drugs tested. The TSC-lap showed no toxicity at the concentration of 40 μg/ml in macrophages, and at 15.6 μg/ml it could increase the phagocytic index. We observed that this compound induced in vitro ultrastructural changes manifested as withered and broken cells beyond a disorganized cytoplasm with accumulation of granules. We did not observe indications of activity in the cell wall, although membrane damages were noted. We observed alterations in the membrane permeability, culminating in a significant increase in K + efflux and a gradual loss of the cellular content with increase in the concentration of TSC-lap. In addition, we showed a significant reduction of ergosterol amount in the Pb18 membrane. These data reinforce the possible mechanism of action of this compound to be closely associated with ergosterol biosynthesis and reaffirms the antifungal potential of TSC-lap against Paracoccidioides spp.